Cryptogenic Pyogenic Liver Abscess Due to Fusobacterium nucleatum in an Immunocompetent Patient - Swaminathan, Neeraja (Eur J Case Rep Intern Med, 2020)
In this case, a 76-year-old female presented with 3–4 days of fever with no other localizing signs. Notably, she had had an untreated Fusobacterium bacteraemia approximately 8 weeks prior to admission. She underwent abdominal imaging which demonstrated a liver abscess and had percutaneous drainage of the same. Blood and pus cultures both grew Fusobacterium nucleatum, which is an unusual organism to be associated with a liver abscess, especially in an immunocompetent host with no risk factors for this condition. Interestingly, this patient did not have any history of dental work, instrumentation, liver function test (LFT) abnormalities and no extrahepatic source for the abscess. This case highlights the importance of having a high index of clinical suspicion for an occult source of infection and emphasizes the importance of following up on cultures even after discharge of a patient, since anaerobic infections such as those caused by Fusobacterium can have a largely indolent course. LEARNING POINTS: Fever of unknown aetiology with prior bacteraemia merits a thorough work-up for occult sources such as a localized abscess or malignancy, which can cause bacterial translocation. Fusobacterium and other anaerobic infectious agents should be considered in the context of an indolent disease course since they are slow-growing in cultures, and also, if the patient has risk factors such as immunosuppression, diabetes, poor oral hygiene and so on. It is important to have systems in place in hospitals to ensure follow-up for patients who may have a positive culture after discharge from hospital to confirm that the infection is adequately addressed.